2013
DOI: 10.1590/1414-431x20132979
|View full text |Cite
|
Sign up to set email alerts
|

A phthalide derivative isolated from endophytic fungiPestalotiopsis photiniae induces G1 cell cycle arrest and apoptosis in human HeLa cells

Abstract: MP [4-(3′,3′-dimethylallyloxy)-5-methyl-6-methoxyphthalide] was obtained from liquid culture of Pestalotiopsis photiniae isolated from the Chinese Podocarpaceae plant Podocarpus macrophyllus. MP significantly inhibited the proliferation of HeLa tumor cell lines. After treatment with MP, characteristic apoptotic features such as DNA fragmentation and chromatin condensation were observed in DAPI-stained HeLa cells. Flow cytometry showed that MP induced G1 cell cycle arrest and apoptosis in a dose-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Many chemotherapeutic drugs induce the expression of TP73, which in turn enhances drug-induced TP73-dependent apoptosis. Several studies have shown the involvement of TP73 in response to phytometabites [ 63 ]. 4-(39,39-dimethylallyloxy)-5-methyl-6-methoxyphthalide (MP) was obtained from the liquid culture of Pestalotiopsis photiniae isolated from the Chinese Podocarpaceae plant Podocarpus macrophyllus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many chemotherapeutic drugs induce the expression of TP73, which in turn enhances drug-induced TP73-dependent apoptosis. Several studies have shown the involvement of TP73 in response to phytometabites [ 63 ]. 4-(39,39-dimethylallyloxy)-5-methyl-6-methoxyphthalide (MP) was obtained from the liquid culture of Pestalotiopsis photiniae isolated from the Chinese Podocarpaceae plant Podocarpus macrophyllus .…”
Section: Discussionmentioning
confidence: 99%
“…4-(39,39-dimethylallyloxy)-5-methyl-6-methoxyphthalide (MP) was obtained from the liquid culture of Pestalotiopsis photiniae isolated from the Chinese Podocarpaceae plant Podocarpus macrophyllus . Flow cytometry showed that MP induced G1 cell cycle arrest and apoptosis, as well as apoptotic morphology of cancer cells in a concentration-dependent manner [ 63 ]. The expression of the TP73 protein was increased after treatment with various MP concentrations [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noscapine, a phthalide isoquinoline alkaloid derived from opium, inhibits cell proliferation by inducing apoptosis in colon cancer cells (40). Furthermore, 4-(3',3'-dimethylallyloxy)-5-methyl-6-methoxyphthalide, which is isolated from Podocarpus macrophyllus, inhibits proliferation of HeLa tumor cell lines by inducing G1 cell cycle arrest and apoptosis (41). No study has investigated the effects of SN, a phthalidelike structure, on cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, it is the second most common cancer affecting women, after breast cancer. Annually, more than 500,000 people are diagnosed with cervical cancer across the world, and it causes the death of 275,000 patients (Chen and Yang, 2013;Nekulova et al, 2013). Tumor protein p73 (TP73, also known as p73) was reported as the first member of the cancer-suppressor TP53 gene family.…”
Section: Introductionmentioning
confidence: 99%